Biological and clinical impact of IL-6 production by ovarian carcinoma cells - Lange, Andrzej; Kryczek, Ilona; Gryboś, Marian (Contemporary Oncology/Współczesna Onkologia, 1999)
In this review article some information is presented regarding of the biological impact of interleukin 6 (IL-6) production by ovarian carcinoma. This is illustrated by elevation of C-reactive protein (CRP) in sera of ovarian carcinoma patients and a fair degree correlation between ascites IL-6 levels and platelet count. IL-6 is physiologically produced by ovarian granulosa cells and this production is regulated by gonadotropin activity. In ovarian carcinoma patients IL-6 production is highly elevated and automonous. This is suggested by higher level of IL-6 generation in carcinomatous than in benign cysts. Ovarian cancer IL-6 generation is associated with tumour morphology; papillare cancers and mucous/serous tumours are good producers of IL-6. Ability of ovarian carcinoma cells to produce IL-6 likely reflects the level of differentiation of ovarian cell which is transformed to carcinoma cell. IL-6 and its reading protein CRP maybe regarded as markers of ovarian tumours with the potential to modulate local immunity.